Time to Live: Christian Formation through the Christian Year - Erickson, Matthew (Journal of spiritual formation & soul care, 2019)
This article examines the role of the Christian, or liturgical, year as one of the simplest yet most powerful ways of spiritually forming people, both individually and corporately, to become more like Jesus. Many Christians and churches are subtly shaped more by the time structures of the average work week or cultural holidays than the life of Christ or the church. The tendency to address individual spiritual formation focuses largely on cognitivist approaches to change or individual formative practices. However, the author explores several ways in which the Christian year offers a wholistic approach to life formation through the steady, time-bound patterns of the Christian year. Engaging both the conscious and unconscious self in cognitive practices and steady habits, both the individual Christian and local congregations are trained toward Christlikeness.